Strike Activity and Wildcat Strikes in British Columbia : 1945-1975 - Fisher, E. (Relations industrielles / Industrial Relations, 1982)
This paper extends and updates the research of Professor Jamieson on strike activity in British Columbia for the period 1945-1975.